A bibliometric analysis of process safety research in China: Understanding safety research progress as a basis for making China's chemical industry more sustainable. (1st August 2020) - Yang, Yunfeng; Chen, Guohua; Reniers, Genserik; Goerlandt, Floris
Abstract: Along with the expansion of China's chemical industry, a series of catastrophic chemical accidents have occurred, often with severe human casualties, resulting in adverse effects on the sustainable development. In line with these developments, process safety research is also developing rapidly in China. This paper aims to present insights in the progress of process safety research in China using bibliometric analysis. The results indicate that in China the most productive authors, institutions, and provinces are located in economically developed coastal areas and in areas with more universities specializing in safety science and engineering. As for the international cooperation, the most significant collaborating countries are economically developed countries or China's neighbors, and these countries have published a large number of papers important in this field. The citation analysis shows that Chinese process safety research currently still has a relatively limited international impact. The analysis of hot topics shows that there currently are very few new methods or research topics introduced in recent years, and there is still significant room for the Chinese research community to improve in some subdomains of the research field. Based on these trends and apparent shortcomings in the literature, future research directions are proposed. The results contribute to understanding the overall situation of process safety research in China, and can serve as a high-level synthesis of the research field. This information is useful for developing research and development policies and industrial strategies, and benefits the safety and sustainability of China's chemical industries. Highlights: The study applies bibliometric analysis in mapping process safety research in China. The most influential Chinese authors, institutes, areas, and papers are identified. National and international cooperation among authors and institutes is analyzed. Hot topics and trends are identified using terms co-occurrence network. Several avenues for future research are proposed based on analysis results.